Efecto del Picloram y el 2,4-D sobre la embriogénesis somática en variedades de caña de azúcar - Díaz Santillán, Graciela Victoria; Di Pauli, Valentina; Cutuli, Fiorella Lourdes Anael; Zalazar, Nicanor Oscar; Canseco, Myriam Ayelen; Fontana, Paola Daniela (Asociación de Biología de Tucumán, 2025)
Poster